The Prison and Transition Health (PATH) cohort study: Prevalence of health, social, and crime characteristics after release from prison for men reporting a history of injecting drug use in Victoria, Australia. (1st October 2021) - Stewart, Ashleigh C.; Cossar, Reece D.; Wilkinson, Anna L.; Quinn, Brendan; Dietze, Paul; Walker, Shelley; Butler, Tony; Curtis, Michael; Aitken, Campbell; Kirwan, Amy; Winter, Rebecca; Ogloff, James; et al.
Highlights: Health and social outcomes for people who inject drugs after release from prison are poorly understood. This study explores health and social outcomes among men with histories of injecting drug use after their release from prison. The proportion of participants reporting high rates of unemployment and homelessness were consistent across study follow-up. After prison release, both a return to injecting illicit substances and involvement in crime-related activities were common. Understanding experiences of this group after release from prison may inform better transitional support programs. Abstract: Background: People who inject drugs are overrepresented in prison and have diverse and complex health needs. However, outcomes after release from prison are poorly understood, limiting effective interventions supporting community reintegration. We describe the prevalence of socio-demographics, physical and mental health, alcohol and other drug use, and crime characteristics of men with histories of injecting drug use after their release from prison in Victoria, Australia. Methods: Data come from the Prison and Transition Health (PATH) prospective cohort study. Interviews were undertaken approximately three, 12, and 24 months after release from their index prison episode and were completed in the community, or in prison for those reimprisoned during the study. We present cross-sectional descriptive statistics for each follow-up wave of the PATH study. Results: Among 400 men recruited into PATH, 85 % (n = 336) completed at least one follow-up interview; 162 (42 %) completed all three interviews. Participants reported social disadvantage and health inequity, including high rates of unemployment, homelessness, and physical and mental health morbidities at each follow-up time point. Rapid return to illicit substance use was common, as was overdose (ranging 9 %–13 %), receptive syringe sharing (ranging 20 %–29 %), involvement in crime-related activities (ranging 49 %–58 %), and reimprisonment (ranging 22 %–50 %) over the duration of follow-up. Conclusion: Men in this study experienced substantial health and social challenges across a 24-month prospective follow-up period. Improved understanding of characteristics and experiences of this group after release from prison can inform more coordinated and continued care between prison and the community.